A family-based approach examining perceptions of an Australian TRYathlon series on children's health and development. (8th November 2022) - Caperchione, Cristina M; English, Madeleine; Sharp, Paul; Stolp, Sean; Wallace, Lee; Harris, David; Ashton, John
Abstract: Regular physical activity supports children's physical and psychological health and wellbeing, and provides opportunities to build social and emotional skills such as resilience, confidence, and self-efficacy. Research has demonstrated that mass participant sporting events can serve as important social and environmental correlates of physical activity. This study sought to explore parents and children's perceived motivations and perspectives of participation in the Australian Sanitarium Weet-Bix Kids TRYathlon (a non-competitive triathlon series), on children's health and well-being. An exploratory qualitative design utilizing seven focus groups were conducted with 27 family units including 31 parents and 61 children (age 7–15 years old). Data were recorded, professionally transcribed and then analyzed using thematic analysis. Three overarching themes were identified, including (1) motivations for event and physical activity participation, revealing social interaction, peer support and friendly competition as motivators for participation as well as parents' interest in supporting the development of healthy habits; (2) Perceived physical activity, fitness, and developmental benefits, detailing changes to the types of physical activity children performed as well as opportunities for children to develop physical skills and competencies; and (3) Perceived psychosocial benefits of participation, highlighting opportunities for children to develop and demonstrate independence and autonomy through event participation. Notably, parents and children identified benefits beyond immediate participation including increased family engagement and social support. Mass participant events hold the potential to elicit a range of benefits for children and their families; however, further efforts may be needed to engage less active or disengaged families. Lay Summary: The physical and psychological benefits of being physically active during childhood are well established. However, most Australian children do not exercise at sufficient levels to receive the full extent of these health benefits. Research has demonstrated that mass participant sporting events can create supportive environments to engage in physical activity and sport whilst promoting mental, social and emotional well-being, but their impact on youth is unknown. Therefore, this study explored parents and children's perceived motivations and perspectives of participation in a mass participant sporting event, the Australian Sanitarium Weet-Bix Kids TRYathlon, on children's health and well-being. Our research indicated a range of motivators for engaging in the event, including social interaction, peer support, friendly competition and parents' interest in supporting healthy habits. The study also highlighted numerous perceived physical and psychosocial benefits of participation, such as increased physical activity pre and post-event, improved physical competency, enhanced confidence and increased family engagement and social support. Nonetheless, we believe further efforts may be needed to engage less active or disengaged families in the Australian Sanitarium Weet-Bix Kids TRYathlon and promote behaviour change.